Carotid endarterectomy with mini-invasive access in locoregionalanaesthesia - De Troia, A.; Mosso, F.; Biasi, L.; Corona, et al., P. (Acta Biomedica Atenei Parmensis, 2008)
Aim: To assess the validity of a carotid endarterectomy (CEA) with a mini-invasive access via a 3-7 cm cutaneous incision in locoregional anaesthesia as a viable alternative to the traditional access with a cutaneous incision longer than 7 cm. Materials and Methods: We carried out a retrospective analysis of 76 consecutive patients (Group A) who had undergone carotid CEA in locoregional anaesthesia with cervical mini-access (3-7 cm incision), compared to a preceding series of 95 patients (Group B) who had undergone the same operation through a traditional access (incision > 7 cm). All patients in Group A were examined solely by means of duplex ultrasound scanning. Results: No mortality occurred in Group A and the morbidity rate was as follows: 1.3% strokes, 2.6% minor neurological events and 6.5% transitory deficit of peripheral nerves. In Group B, the mortality rate was 1%, with the following morbidity rate: 2% strokes, 1% minor neurological events and 7.3% transitory deficit of peripheral nerves. Statistical analysis revealed the two groups as being compatible for age, sex, associated pathologies and type of surgery. No statistically significant differences emerged between the two series of patients with regards to neurological morbidity or operative mortality. Conclusions: In addition to being more aesthetically pleasing, mini-invasive access is a viable alternative to the traditional access for patients undergoing carotid CEA in locoregional anaesthesia.